Association between mental demands at work and cognitive functioning in the general population - results of the health study of the Leipzig research center for civilization diseases (LIFE). - Then, F. S.; Luck, T.; Luppa, M.; Arelin, K.; Schroeter, M. L.; Engel, C.; Loffler, M.; Thiery, J.; Villringer, A.; Riedel-Heller, S. G. (J Occup Med Toxicol, 2014)
BACKGROUND: The level of mental demands in the workplace is rising. The present study investigated whether and how mental demands at work are associated with cognitive functioning in the general population. METHODS: The analysis is based on data of the Health Study of the Leipzig Research Centre for Civilization Disease (LIFE). 2,725 participants aged 40-80 years underwent cognitive testing (Trail-Making Test, Verbal Fluency Test) and provided information on their occupational situation. Participants over the age of 65 years additionally completed the Mini-Mental State Examination. Mental demands at work were rated by a standardized classification system (O*NET). The association between mental demands and cognitive functioning was analyzed using Generalized Linear Modeling (GENLIN) adjusted for age, gender, self-regulation, working hour status, education, and health-related factors. RESULTS: Univariate as well as multivariate analyses demonstrated significant and highly consistent effects of higher mental demands on better performance in cognitive testing. The results also indicated that the effects are independent of education and intelligence. Moreover, analyses of retired individuals implied a significant association between high mental demands at work of the job they once held and a better cognitive functioning in old age. CONCLUSIONS: In sum, our findings suggest a significant association between high mental demands at work and better cognitive functioning. In this sense, higher levels of mental demands - as brought about by technological changes in the working environment - may also have beneficial effects for the society as they could increase cognitive capacity levels and might even delay cognitive decline in old age.